Raw Material Inventory Control Using The Period Order Quantity (POQ) Method to Reduce Stockout and Overstock Risks - Achmad Suryadi Nasution; Okto Bryan Simbolon; Triyana Muliawati; Tiara Shofi Edriani; Dear Michiko Mutiara Noor; Rifky Fauzi (Vygotsky: Jurnal Pendidikan Matematika dan Matematika, 2025)
The rapid growth of coffee shops in Lampung has increased demand for Robusta Lampung, Arabica Kerinci, and Arabica Aceh Gayo, causing stockouts and overstocking at a coffee roastery. This study uses the Period Order Quantity (POQ) method to optimize inventory by ordering based on predictable demand periods, reducing order frequency and costs. Using demand data from the last six months of the year, POQ outperforms the manual inventory policy. Assuming a 5% holding cost and 90%–99% service levels (ensuring product availability), POQ reduces costs by 0.119%–0.163%, boosting profitability. Adopting POQ with real-time demand tracking can balance inventory and meet rising demand.